2007
DOI: 10.1111/j.1464-410x.2007.07357.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a synchronous twin‐pulse technique for shock wave lithotripsy: a prospective randomized study of effectiveness and safety in comparison to standard single‐pulse technique

Abstract: OBJECTIVE To asses the efficacy and safety of bidirectional synchronous twin‐pulse extracorporeal shock wave lithotripsy (ESWL) compared with standard ESWL. PATIENTS AND METHODS Between March 2003 and December 2006, 240 patients with a radio‐opaque single renal stone of ≤25 mm were randomized to treatment either by the Twinheads (TH) lithotripter (FMD, Lorton, Virginia, USA) or the Dornier Lithotripter S (DLS, Dornier MedTech Europe GmbH, Germering, Germany). Before and after ESWL, urinary N‐acetyl‐B‐glucosami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Dual-head lithotripters are already being used to treat patients and despite the inherent complexity associated with twin shock sources—two potential sources of variability in coupling and acoustic output—plus concern that treatment at very fast shock-wave rate (up to 240 shock waves per min) might be injurious, initial reports suggest that such machines can be used safely and effectively 80,81. Dual-head lithotripters are not currently in widespread use, but the concept has merit and with continued refinement and further study such machines may be applied more widely in the future.…”
Section: Lithotripter Technologymentioning
confidence: 99%
“…Dual-head lithotripters are already being used to treat patients and despite the inherent complexity associated with twin shock sources—two potential sources of variability in coupling and acoustic output—plus concern that treatment at very fast shock-wave rate (up to 240 shock waves per min) might be injurious, initial reports suggest that such machines can be used safely and effectively 80,81. Dual-head lithotripters are not currently in widespread use, but the concept has merit and with continued refinement and further study such machines may be applied more widely in the future.…”
Section: Lithotripter Technologymentioning
confidence: 99%
“…Taken together, ESWL trauma is regarded to cause scar formation and loss of functional renal mass 14. In contrast, however, other recent studies reported that renal function impairment associated with ESWL is largely resolved within 1 to 3 months and ESWL per se has no significant long-term effects on renal function 17,18. However, the patients included in these studies had normal renal function, and the effect of ESWL in CKD patients was not addressed.…”
Section: Discussionmentioning
confidence: 96%
“…[1415] The rationale in this concept is, that “filling” the negative part of the pressure wave with a positive pressure pulse would theoretically result in improved fragmentation and reduced cavitation with reduced parenchymal damage.…”
Section: Shockwave Sourcesmentioning
confidence: 99%